2017
DOI: 10.1021/acs.biochem.6b01170
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Interdomain Interactions in the Conformational Change and Catalytic Mechanism of Endoplasmic Reticulum Aminopeptidase 1

Abstract: Endoplasmic reticulum aminopeptidase 1 (ERAP1) is an intracellular enzyme that is important for the generation of antigenic epitopes and major histocompatibility class I-restricted adaptive immune responses. ERAP1 processes a vast variety of different peptides but still shows length and sequence selectivity, although the mechanism behind these properties is poorly understood. X-ray crystallographic analysis has revealed that ERAP1 can assume at least two distinct conformations in which C-terminal domain IV is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 48 publications
(121 reference statements)
7
47
0
Order By: Relevance
“…Alternative modes of caspase-2 activation have since been proposed depending on the type of cellular death signals (review (50)); in these cases it is tempting to speculate that CARD:core interactions may play a role in regulating caspase-2 function, should they be present. Interdomain interactions have been demonstrated to be critical in controlling the different conformational states and in regulating the catalytic activity of several proteins including the deubiquitinating enzyme USP4 (51), phenylalanine hydroxylase (52) and ERAP-1 (endoplasmic reticulum aminopeptidase-1) (53). …”
Section: Discussionmentioning
confidence: 99%
“…Alternative modes of caspase-2 activation have since been proposed depending on the type of cellular death signals (review (50)); in these cases it is tempting to speculate that CARD:core interactions may play a role in regulating caspase-2 function, should they be present. Interdomain interactions have been demonstrated to be critical in controlling the different conformational states and in regulating the catalytic activity of several proteins including the deubiquitinating enzyme USP4 (51), phenylalanine hydroxylase (52) and ERAP-1 (endoplasmic reticulum aminopeptidase-1) (53). …”
Section: Discussionmentioning
confidence: 99%
“…Sodium ions were added to neutralize the total charge of the systems and ff14SB parameters were applied using the LEaP module of AMBER (67). The equilibration method of 10 ns and simulation parameters were as described in (68). After 1 ns equilibration of the systems at 300 K under isothermal-isobaric ensemble (NPT) conditions, production runs of 500 ns were performed in the canonical ensemble (NVT).…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Recent experimental analysis of the solution structure of ERAP1 using small-angle X-ray scattering (SAXS) revealed that, in solution, the average structure of ERAP1 corresponds well with the crystallographically observed open conformation ( 32 ). This analysis was performed with ligand-free enzyme and is, therefore, consistent with the proposal that “open” ERAP1 is the substrate-capture conformation and that substrate binding promotes the conformational shift to “closed” ERAP1 that facilitates catalysis ( 17 , 29 ).…”
Section: Overall Structure and Conformational Changesmentioning
confidence: 99%